2019
DOI: 10.1111/hsc.12797
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of home care nurses in Canada: A scoping review

Abstract: Nurses are among the largest providers of home care services thus optimisation of this workforce can positively influence client outcomes. This scoping review maps existing Canadian literature on factors influencing the optimisation of home care nurses (HCNs). Arskey and O'Malley's five stages for scoping literature reviews were followed. Populations of interest included Registered Nurses, Registered/Licensed Practical Nurses, Registered Nursing Assistants, Advanced Practice Nurses, Nurse Practitioners and Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 91 publications
(215 reference statements)
1
47
2
6
Order By: Relevance
“…Stress at work created mental strain and lead to multitasking, a lack of focus, rushing, moving too fast and an increased risk and fear of falling and injuries [28,31]. These findings have also been mentioned by other researchers [11,13,15]. Excessive sick leave was reported as a problem in home care [39].…”
Section: Organisational Aspects Of Home Care Workmentioning
confidence: 78%
See 1 more Smart Citation
“…Stress at work created mental strain and lead to multitasking, a lack of focus, rushing, moving too fast and an increased risk and fear of falling and injuries [28,31]. These findings have also been mentioned by other researchers [11,13,15]. Excessive sick leave was reported as a problem in home care [39].…”
Section: Organisational Aspects Of Home Care Workmentioning
confidence: 78%
“…Those studies reported that low wages and minimal benefits are typical features of home care work and are often a source of job dissatisfaction [11,13,15]. Time pressure during hectic workdays [26,27,33,37,39,52,53] and increased indirect work task are sources of negative emotions such as frustration, stress, workload and overtime hours [34,47,51,53].…”
Section: Organisational Aspects Of Home Care Workmentioning
confidence: 99%
“…These findings highlight that, despite examples of excellence, at the system level there are ongoing and significant barriers to patient- and family-centred home-care provision for this population in Ontario. This is an international trend in countries with similar home-care provision to Canada due to many factors, including: demands for services greater than existing funding mechanisms; human resource challenges, including recruitment and retention in the home-care sector; lack of system integration ( Farmanova et al, 2019 ; Ganann et al, 2019 ; Markle-Reid et al, 2017 ; Province of British Columbia, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Hudson et al [22], role understanding is an integral part of teamwork because it generates trust and mutual respect. Greater understanding of others' roles in the team promotes role clarity to foster optimal utilization of all professional roles and improve patient outcomes and health system cost-effectiveness [23]. Hence, role clarity is key to effective team training interventions.…”
Section: Introductionmentioning
confidence: 99%